Continent. Year 1: A Selection of Issues 1.1-1.4 - Allen, Jamie; Boshears, Paul; van Gerven Oei, Vincent W.J; Groves, Adam Staley; Jenkins, Nico (punctum books, 2012)
continent. Year 1: A selection of issues 1.1-1.4 collects a variety of thoughts and tropes from the 2011 issues of continent., ranging from work on Greek poetry to deep brain recordings, from speculative realism to the fragments as a unit of prose, and from queer theory to mass murder. This collection presents the fruits of an intense collaboration throughout the different zones of the Academy